Proceso atención de enfermería en paciente de 49 años con hemorragia digestiva alta - Arias Baños, Carla Cinthya (2021)
The loss of blood from the upper digestive tract corresponds to the region between the sphincter of the esophagus and the angle of treitz, one of the typical symptoms is the presence of blood in the stool and vomit and rarely the presence of blood from of the lower digestive tract, its prevalence occurs more in the male gender than in the female sex, the constancy of its appearance depends on various factors such as the presence of underlying pathologies, the administration of digestive disorders, its etiology is diverse which include: Gastric ulcer in 50% of cases, inflammation of the esophagus, stomach, duodenum, appearance of esophageal varices, marllory wess tears and in the worst case digestive tumors, it is for these causes that it is considered one of the most surgical emergencies. important that deserve income. The present clinical study demonstrates the provision of nursing care in patients with upper gastrointestinal bleeding through the application of the nursing care process based on scientific basis, in a comprehensive and systematic, humanistic way, with the aim of providing quality care and characteristic warmth in the nursing staff. The real health needs of the individual were identified and prioritized through an assertive and timely clinical nursing judgment, to later apply the care that contributed to the recovery of their health status. This clinical study is focused on individuals with unknowns about the management of patients with upper gastrointestinal bleeding in order to increase the degree of knowledge.